IMPLEMENTASI SUKUK UNTUK MENDORONG PERKEMBANGAN EKONOMI DI INDONESIA PADA PASAR MODAL SYARIAH - Wahid Wachyu Adi Winarto Wachyu (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2021)
Sukuk is one of the most innovative products in the development of the contemporary Islamic financial system. The purpose of writing this article is to determine the development of sukuk in encouranging economic development in Indonesia od the Islamic capital market in 2015-2020. The development of sukuk continues to increase from year to year according to Islamic capital market statistics. With the content analysis method. From the result of the sukuk data has an effect on economic development in Indonesia.